2020
DOI: 10.1021/acs.est.0c01970
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget Discovery of 11 Aryl Organophosphate Triesters in House Dust Using High-Resolution Mass Spectrometry

Abstract: There is growing interest in the identification of novel aryl organophosphate triester (OPTE) congeners that may exist in the environment. In this study, we discovered 11 novel aryl OPTEs in north China house dust using a characteristic aryl phosphate fragment-guided high-resolution mass spectrometry method with data-independent acquisition. Tripentylated triphenyl phosphate (TPeTPhP), dicresyl phenyl phosphate (DCrPP), diisodecylphenyl phosphate (DIDPP), butoxyethoxyethyl octyl phenyl phosphate (BEEOPP), dioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 24 publications
5
56
0
Order By: Relevance
“…Data processing for functional group-dependent screening was accomplished using Xcalibur’s Qual Browser software. Functional group-dependent screening was based on nine feature fragment ions of OPEs reported in previous studies. , The nine fragment ions were triphenyl phosphate ion (C 18 H 16 O 4 P + ), diphenyl phosphate ion (C 12 H 12 O 4 P + ), monophenyl phosphate ion (C 6 H 8 O 4 P + ), phosphate ion (H 4 O 4 P + ), diphenyl phosphate dehydrated form ion (C 12 H 10 O 3 P + ), dicresyl phosphate ion (C 14 H 16 O 4 P + ), dicresyl phosphate dehydrated form ion (C 14 H 14 O 3 P + ), cresyl phenyl ion (C 13 H 14 O 4 P + ), and phosphonate dianion ion (H 2 O 3 P + ). The structures of these nine fragment ions are supplied in Table S5.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data processing for functional group-dependent screening was accomplished using Xcalibur’s Qual Browser software. Functional group-dependent screening was based on nine feature fragment ions of OPEs reported in previous studies. , The nine fragment ions were triphenyl phosphate ion (C 18 H 16 O 4 P + ), diphenyl phosphate ion (C 12 H 12 O 4 P + ), monophenyl phosphate ion (C 6 H 8 O 4 P + ), phosphate ion (H 4 O 4 P + ), diphenyl phosphate dehydrated form ion (C 12 H 10 O 3 P + ), dicresyl phosphate ion (C 14 H 16 O 4 P + ), dicresyl phosphate dehydrated form ion (C 14 H 14 O 3 P + ), cresyl phenyl ion (C 13 H 14 O 4 P + ), and phosphonate dianion ion (H 2 O 3 P + ). The structures of these nine fragment ions are supplied in Table S5.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Functional group-dependent screening was based on nine feature fragment ions of OPEs reported in previous studies. 22,23 The structures of these nine fragment ions are supplied in Table S5.…”
Section: Sample Extraction and Cleanupmentioning
confidence: 99%
See 1 more Smart Citation
“…Data-independent acquisition (DIA) is a tandem MS/MS method in which all the ions within a selected m/z range are fragmented, and all the produced fragments are analyzed. This full-coverage and nontargeted technique can overcome the bias in the selection of precursors. …”
Section: Introductionmentioning
confidence: 99%
“…Current information on the indoor environmental occurrence of CAEs suggests that CAEs are ubiquitous in indoor dust samples with high detection frequencies and contamination levels. For instance, Christia et al analyzed two commonly used CAEs, namely, acetyl triethyl citrate (ATEC) and tributyl- O -acetyl citrate (ATBC), in n = 54 dust samples collected from Belgium, The Netherlands, Ireland, and Sweden and found that ATBC was detectable in all analyzed samples with a concentration range of 220–119,000 ng/g . Subedi et al determined the concentrations of both phthalate and nonphthalate plasticizers in n = 28 dust samples from three different indoor environments across the United States and reported that ATBC accounted for 49% of the total loads of all measured plasticizers .…”
Section: Introductionmentioning
confidence: 99%